Pre-service elementary teacher’s digital literacy with cognitive style and self-regulated learning - Dede Salim Nahdi; Ujiati Cahyaningsih; Mohamad Gilar Jatisunda; Vici Suciawati; Davi Sofyan (Universitas Majalengka, 2022)
The Covid-19 pandemic has forced many educational institutions to implement online learning through distance learning. However, there are many obstacles that occur in its implementation, one of which is the low level of digital literacy as a mandatory ability in distance learning. This study aims to determine students' digital literacy skills based on factors within students, namely the ability of Cognitive Style and Self-Regulated Learning. This study uses a quantitative approach, with the type of expost facto research. The population in this study were all prospective elementary school teacher students at one of the universities in Majalengka Regency who carried out distance learning, with a sample of 33 respondents. Data were collected using a questionnaire in the form of a digital literacy ability questionnaire, cognitive style and self-regulated learning during distance learning. The results showed that students with cognitive style and self-regulated learning in the high category had better digital literacy skills than the medium and low categories. The conclusion obtained from this study is that Cognitive style and self-regulated learning affect digital literacy skills.